Standardy ochrony małoletnich (SOM) w podmiotach świadczących usługi hotelarskie – aspekt teoretyczny i praktyczny - Ambrożuk-Wesołowska, Dorota; Michałowska, Kinga (PRAWO i WIĘŹ, 2024)
From August 15, 2024, every entity providing hotel services in facilities where minors may or do stay is obliged to have and use the so-called standards for the protection of minors (SPM). This document should include policies and procedures to protect children from harm. In the case of hotel facilities, the most important thing is to develop rules and procedures regarding the relationship between minors and the staff of the facility, as well as the identification of the minor and his relationship with the adult with whom he is staying in the facility. The legislator, introduced the above-mentioned responsibilities, but did not provide any instructions on how to implement them. Meanwhile, the obligation to identify a minor and his relationship with the adult in the facility may cause difficulties in practice. The paper indicates related problems and ways of solving them. It is also considered necessary for the legislator to intervene urgently in this matter, by directly specifying the personal data that a hotel establishment may request in order to comply with the obligation imposed on it.